(untitled) (Journal of Organizational Psychology, 2021)
This article focuses on the role of knowledge management and organizational learning in e-commerce firms as they develop and prosper; theoretical and applied issues of balancing exploration and exploitation for their survival, growth, and profitability are discussed. Knowledge management is presented as central to learning that facilitates long-term success. The concept of micro-formalization related to Agile management practices is proposed as an approach that allows young companies in dynamic sectors to implement learning systems with an adequate but minimal level of formalization without experiencing crises inherent to traditional life-cycle models, and without resorting to rigid procedures which stifle creativity.